2022
DOI: 10.1038/s41598-022-21839-4
|View full text |Cite|
|
Sign up to set email alerts
|

Butein promotes ubiquitination-mediated survivin degradation inhibits tumor growth and overcomes chemoresistance

Abstract: Overexpression of survivin is frequently observed in human malignancies and is associated with poor prognosis. The present study found that survivin is highly expressed in nasopharyngeal carcinoma (NPC) tumor tissues. Depleting survivin with shRNA inhibited cell viability, colony formation, and in vivo tumorigenesis of NPC cells. With a natural product screening, we identified Butein as a potential anti-tumor compound for NPC by reducing survivin protein level. Butein shortened the half-life of survivin and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…FBXL7, an F-box protein that binds to substrates via SKP1-Cullin-1-F-box (SCF) E3 ubiquitin ligase, could enhance polyubiquitylation and degradation of substrates in tumor occurrence and aggression ( Wang et al, 2022 ). Additionally, FBXL7 reduces chemotherapy resistance by promoting the ubiquitination and degradation of survivin ( Dong et al, 2022 ). IDO-targeting PROTAC peptide (IPP), generated and activated from UPS, leads to the activation of effector T cells that could further suppress tumor growth and metastasis ( Zhang C. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…FBXL7, an F-box protein that binds to substrates via SKP1-Cullin-1-F-box (SCF) E3 ubiquitin ligase, could enhance polyubiquitylation and degradation of substrates in tumor occurrence and aggression ( Wang et al, 2022 ). Additionally, FBXL7 reduces chemotherapy resistance by promoting the ubiquitination and degradation of survivin ( Dong et al, 2022 ). IDO-targeting PROTAC peptide (IPP), generated and activated from UPS, leads to the activation of effector T cells that could further suppress tumor growth and metastasis ( Zhang C. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…uncovered that butein can inhibit NPC cells by downregulating survivin through an Akt-Wel CDK1 signal-dependent mechanism. 34 impeding CRC progression. 39 Another crucial regulatory mechanism, the MAPK signaling pathway, exerts control over a wide array of physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Its potent antioxidant, anti‐inflammatory and antitumor properties have been demonstrated across a spectrum of human tumors 14 . For instance, Dong et al uncovered that butein can inhibit NPC cells by downregulating survivin through an Akt‐Wel CDK1 signal‐dependent mechanism 34 . Similarly, Yang et al reported that butein induces apoptosis in ovarian cancer cells by activating both exogenous and endogenous pathways 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Butein inhibited the Akt‐Wee1‐CDK1 signaling pathway, reduced survivin Thr34 phosphorylation, and promoted E3 ligase FBXL7‐mediated survivin ubiquitination and degradation. Moreover, Butein alone or combined with cisplatin overcame the chemotherapy resistance of NPC xenografts (Dong et al., 2022).…”
Section: Natural Products That Target Nasopharyngeal Carcinomamentioning
confidence: 99%